Mapping the Integration of Sustainable Tourism Policy and Post-Disaster Dark Tourism within the SDGs Agenda: A Bibliometric Analysis - Lunariana Lubis; Moh. Musleh; Deasy Arieffiani; Abubakar Ahmad Haruna (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
This study aims to map the development, trends, collaboration patterns, and research gaps related to the integration of sustainable tourism, dark tourism, and post-disaster tourism within the framework of the Sustainable Development Goals (SDGs). The research employs a quantitative approach based on bibliometric analysis of 1,083 publications retrieved from the Dimensions database using structured keyword queries. The data were analyzed using VOSviewer to generate network, density, temporal trend, and collaboration visualizations across authors, institutions, and countries. The findings indicate that publication trends are fluctuating, with noticeable increases during certain periods, reflecting the dynamic evolution of research interest in this field. The dominant research themes revolve around policy, governance, and management, with key terms such as policy, governance, and management appearing most frequently. Network analysis reveals that research collaboration remains concentrated in specific countries and leading institutions, while the participation of developing countries is relatively limited. Furthermore, the study identifies that the conceptual integration between sustainable tourism, dark tourism, and post-disaster tourism has not yet been comprehensively developed within the existing literature. The study concludes that there is a critical need to strengthen integrative approaches in both research and policy to support the achievement of the SDGs. This research contributes by providing a systematic mapping of the knowledge structure and identifying future research directions in sustainable tourism studies.